Theory of simple liquids - Hansen, Jean-Pierre, 1942- (Academic Press, 1990)
This book gives a comprehensive and up-to-date treatment of the theory of "simple" liquids. The new second edition has been rearranged and considerably expanded to give a balanced account both of basic theory and of the advances of the past decade. It presents the main ideas of modern liquid state theory in a way that is both pedagogical and self-contained. The book should be accessible to graduate students and research workers, both experimentalists and theorists, who have a good background in elementary mechanics. Key Features * Compares theoretical deductions with experimental results * Molecular dynamics * Monte Carlo computations * Covers ionic, metallic, and molecular liquids